Resolving Optical and Catalytic Activities in Thermoresponsive Nanoparticles by Permanent Ligation with Temperature‐Sensitive Polymers. Issue 34 (11th July 2019) - Chen, Yihuang; Wang, Zewei; Harn, Yeu Wei; Pan, Shuang; Li, Zili; Lin, Shaoliang; Peng, Juan; Zhang, Guangzhao; Lin, Zhiqun
Abstract: Thermoresponsive nanoparticles (NPs) represent an important hybrid material comprising functional NPs with temperature‐sensitive polymer ligands. Strikingly, significant discrepancies in optical and catalytic properties of thermoresponsive noble‐metal NPs have been reported, and have yet to be unraveled. Reported herein is the crafting of Au NPs, intimately and permanently ligated by thermoresponsive poly( N ‐isopropylacrylamide) (PNIPAM), in situ using a starlike block copolymer nanoreactor as model system to resolve the paradox noted above. As temperature rises, plasmonic absorption of PNIPAM‐capped Au NPs red‐shifts with increased intensity in the absence of free linear PNIPAM, whereas a greater red‐shift with decreased intensity occurs in the presence of deliberately introduced linear PNIPAM. Remarkably, the absence or addition of free linear PNIPAM also accounts for non‐monotonic or switchable on/off catalytic performance, respectively, of PNIPAM‐capped Au NPs. Abstract : Star‐shaped : A general strategy leads to the creation of permanently ligated thermoresponsive nanoparticles with tunable dimensions and compositions by utilizing a rationally designed starlike diblock copolymer (PNIPAM) as a nanoreactor. Studies of the nanoparticles, showing two seemingly contradictory observations on both temperature‐dependent optical and catalytic properties, have led to the reconciliation of data. LCST=lower critical solution temperature.